Analysis Of Enterprise Resources Planning (ERP) Implementation Planning In Car Parts Distributor Companies (Case Study: CV. Persatuan Putra Mandiri) - Yudi Harianto; Kautsar Aryayi; Dwi Oktaviyani; Fahrul Rozi (International Journal of Informatics, Economics, Management and Science (IJIEMS), 2023)
CV Persatuan Putra Mandiri is one of the distributors engaged in the sale of vehicle parts, especially cars. This company uses accounting software to manage its daily business activities, but in its implementation, there are still obstacles that can hinder the development of this company itself. The purpose of this research is to provide clear knowledge to the company regarding the weaknesses and strengths that exist in the current system and help companies to determine which ERP system is suitable for the company and its implementation process to the company's business processes. Therefore, this ERP planning stage begins with identifying problems, identifying ongoing business processes and then making system proposals that are described using Business Process Model Notation (BPMN). The next stage is to analyze the ERP system that may be able to accommodate the overall business process. The method that the author uses in this research is descriptive qualitative, where we obtain data from the description of the existing business processes and by conducting interviews with direct sources, namely employees in the company. We did a comparison of several ERP software commonly used in similar companies, and we got the results where the most suitable ERP software for this research is Oracle because it feels best suited to the needs and conditions of the existing business processes in the company.